Social Capital in Dealing with Flood Disasters in Genuk Sub-District, Semarang City - Kiswoyo, Gandisa Pangestuti; Suwitri, Sri; Yuniningsih, Tri (PERSPEKTIF, 2025)
Flooding is the most common disaster in Indonesia. Flooding has great potential to hit Semarang City, especially Genuk Sub-district which is located in a coastal area. The community is the party that is often harmed when a flood occurs. Social capital is important because it is needed to build a resilient community in the face of disasters. This study aims to analyze social capital in facing flood disaster in Genuk Sub-district through the aspects of trust, norms, and networks. The research method used is descriptive qualitative through interviews, observation, and documentation. The results showed that the social capital of Genuk community is still not optimal in the aspects of trust, norms, and networks. The community's trust in the government and religious leaders is still experiencing obstacles. Existing norms are not yet binding and supervision is limited. The network formed is still hampered by the role of the community and the private sector in contributing to protecting the environment. Recommendations in the research are to collaborate by involving the entire community as the subject of empowerment starting from the younger generation, providing disaster training in formal education, forming volunteers at the community level.